(3GdeSGFd GdehUdjGJ GdKGdKI hCLhHJgGs - (3GdTQja GdeQJVj , CHh GdbGSe,J (B436 (3g` s ((3eMeO Hf GdTjN WGgQ GdSeGhi s)
(3ChdgG (B:s
(3bO GLHJ GOGe dg dce GdSdGeI Yf GdeSGFd GdJi hUdJ Edi s
(3BNQgG (B:s
(3Ef Mce GdcJGHI HGb de jRd dGf GdYHO EPG COi HYV eGYdjg agh eSJQb s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B278 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B81s
Keywords: (3abg GdePGgH GdCNQis